Prevalensi Fasciolosis pada Sapi di Rumah Potong Hewan Ambon - Labetubun, Jusak; Tagueha, Astri Dwyanti (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background: Fasciola spp. are well-known parasites with outstanding adaptation, contributing to infection among various ruminants, and causing zoonotic infections worldwide over the last three decades,  especially in developing countries. However, their presence has been underestimated as a public health concern. The slaughterhouse is an authorized facility that provides safe and healthy meat; therefore, routine inspection for any zoonotic disease should be performed. Purpose: This study aimed to assess the prevalence of fasciolasis in cattle at an Ambon slaughterhouse. Methods: Fresh feces were collected from 42 cattle and the presence of Fasciola spp. using the sedimentation method. Data were descriptively analyzed, and Fisher’s exact test and odds ratio analysis were used to identify the association between risk factors. Results: The overall prevalence of fasciolasis was found to be 7.14%. Cattles > 2 years old were 5.33 times more at risk than younger ones, while cattle from Seram Island were 13 times more susceptible to fasciolasis. No noticeable discrepancies were observed in the prevalence rates of bulls and cows. This study revealed that infection occurred before cattle departure, which started at their origin and was associated with age as an intrinsic factor. The physiological status, geographic conditions, and management systems are predicted to provide a suitable niche for the parasite life cycle. Conclusion: Although the rate of infection was low, it should be considered a risk and appropriately handled before sale. As this study was the first to investigate Fasciola infection in Ambon slaughterhouses, further studies are recommended to reveal other possible risk factors.